2023
DOI: 10.1038/s41467-023-37957-0
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic fluctuations in a bacterial metabolic network

Abstract: The operation of the central metabolism is typically assumed to be deterministic, but dynamics and high connectivity of the metabolic network make it potentially prone to generating fluctuations. However, time-resolved measurements of metabolite levels in individual cells that are required to characterize such fluctuations remained a challenge, particularly in small bacterial cells. Here we use single-cell metabolite measurements based on Förster resonance energy transfer, combined with computer simulations, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 79 publications
2
3
1
Order By: Relevance
“…This finding was consistent with considerable fluctuation in intracellular pyruvate levels observed in starved E. coli cells expressing a CFP-PdhR-YFP-based pyruvate sensor when exposed to glucose . Interestingly, fructose also exhibited a response curve similar to that of glucose, suggesting that S.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…This finding was consistent with considerable fluctuation in intracellular pyruvate levels observed in starved E. coli cells expressing a CFP-PdhR-YFP-based pyruvate sensor when exposed to glucose . Interestingly, fructose also exhibited a response curve similar to that of glucose, suggesting that S.…”
Section: Resultssupporting
confidence: 82%
“…The result was discrepant from the early finding that the response curves of pyruvate and glucose matched in E. coli . This finding may be explained by the complex pyruvate transport system in yeast cells compared to that in E.…”
Section: Resultscontrasting
confidence: 80%
See 1 more Smart Citation
“…The negative feedback loop leading to the oscillation was not caused by inhibition through the final product (butanol), as the authors showed by artificially increasing butanol levels in the reactor. The oscillation might be similar to oscillations observed in the glycolysis pathway in yeast or bacteria mediated by redox coenzyme couples (ATP/ADP and NADH/NAD) and via both intraand intercellular acetaldehyde [39,40].…”
Section: Metabolic Oscillation In Clostridium Pasteurianumsupporting
confidence: 55%
“…A test for the involvement of the TCA cycle focused on pyruvate, the end product of glycolysis. Even after knocking out pykF , the major gene responsible for production of pyruvate from glycolysis, 0.1% glucose still caused a 100- to 1,000-fold increase in survival during ciprofloxacin treatment (Figure S3B). These data indicate that glucose-mediated tolerance is maintained in the pykF mutant.…”
Section: Glucose Confers E Coli Tolerance To Quinolones Aminoglycosid...mentioning
confidence: 99%